The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1186/s12887-023-04180-1
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil for congenital heart diseases induced pulmonary hypertension, a meta-analysis of randomized controlled trials

Abstract: Background Sildenafil was first prescribed for angina pectoris and then for erectile dysfunction from its effects on vascular smooth muscle relaxation and vasodilatation. Recently, sildenafil has been proposed for congenital heart diseases induced pulmonary hypertension, which constitutes a huge burden on children's health and can attribute to fatal complications due to presence of unoxygenated blood in the systemic circulation. Therefore, our meta-analysis aims to further investigate the safet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…[1] Recent improvements in medical treatments, surgical procedures, imaging, and pediatric intensive care helped more than 90% of congenital heart disease (CHD) children reach adulthood and decreased the total mortality rate by 31%in the previous 20 years. [2,3] This changes our focus on CHD from mortality to morbidity, where although babies born with CHD now have a longer life expectancy and better quality of life, they are more likely to have psychological distress, neurocognitive deficits, and social challenge. Studies reported Medicine that approximately 30% had mood or anxiety disorders and 20% showed symptoms comparable with posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Recent improvements in medical treatments, surgical procedures, imaging, and pediatric intensive care helped more than 90% of congenital heart disease (CHD) children reach adulthood and decreased the total mortality rate by 31%in the previous 20 years. [2,3] This changes our focus on CHD from mortality to morbidity, where although babies born with CHD now have a longer life expectancy and better quality of life, they are more likely to have psychological distress, neurocognitive deficits, and social challenge. Studies reported Medicine that approximately 30% had mood or anxiety disorders and 20% showed symptoms comparable with posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%